Discussion on operation: To compare the curative effect of PMT and CDT in the treatment of middle and high risk stratified APE and the clinical application value of serum BNP, TnI and plasma DFR levelse - Guan, Qinglong; Liu, Chenglong; Li, Wei; Wang, Xiaofei; Gu, Ruiyuan; Wang, Ruihua; Li, Gang; Liu, Shuai (Frontiers in Surgery, 2023)
Objective To compare the efficacy of Percutaneous mechanical thrombectomy (PMT) and Catheter directed thrombolysis (CDT) in the treatment of patients with moderate and high-risk ape and explore the clinical application value of biomarkers in the treatment of moderate and high-risk ape. Method A total of 84 patients with ape were selected from the Department of vascular surgery of the Second Affiliated Hospital of Shandong First Medical University and the Department of vascular surgery of Shanghai Ninth People's Hospital Affiliated with Shanghai Jiao Tong University School of Medicine. According to the relevant guidelines, they were divided into high-risk and medium-risk groups, including PMT groups (35 cases) and CDT groups (49 cases). To detect the changes of serum B-type brain natriuretic peptide (BNP),Troponin I (TnI) and plasma D-dimer/fibrinogen ratio (DFR) levels in different risk stratification before and after PMT and CDT, the correlation and diagnostic value of each index, and compare the thrombus clearance rate, pulmonary artery pressure, average dosage of urokinase, effective thrombolytic time, average hospitalization time and complications of PMT and CDT. Result Under different treatment methods and risk stratification, there was no statistically significant difference in the clinical data of patients at general baseline;The preoperative BNP, TnI and DFR levels of PMT and CDT in the middle and high risk stratification were significantly lower than those in the other groups (P < 0.005),Compared with the CDT group, PMT has significantly better therapeutic effect on ape than the CDT group in terms of thrombus clearance rate, pulmonary artery pressure, average dosage of urokinase, effective thrombolytic time and average hospitalization time (P < 0.05),meanwhile,there was no significant difference in postoperative complications between the two groups (P < 0.05). After half a year of follow-up, the levels of BNP, TnI and DFR in the cured group were significantly lower than those in the effective group and the ineffective group. The areas under the curve of serum BNP, TnI and plasma DFR were 0.91, 0.87 and 0.93 and the area under the curve DFR has higher diagnostic efficiency than BNP and TnI, while the sensitivity and specificity of TnI are significantly higher than BNP and DFR. Conclusion Serum BNP, TnI and plasma DFR levels can reflect the risk stratification and better clinical diagnostic value of ape,PMT and CDT are used to treat high-risk ape. For hospitals with medical conditions, PMT is more worthy of clinical recommendation.